A 3D reconstruction method of the body envelope from biplanar X-rays: Evaluation of its accuracy and reliability. Issue 16 (16th December 2015) - Nérot, Agathe; Choisne, Julie; Amabile, Célia; Travert, Christophe; Pillet, Hélène; Wang, Xuguang; Skalli, Wafa
Abstract: The aim of this study was to propose a novel method for reconstructing the external body envelope from the low dose biplanar X-rays of a person. The 3D body envelope was obtained by deforming a template to match the surface profiles in two X-rays images in three successive steps: global morphing to adopt the position of a person and scale the template׳s body segments, followed by a gross deformation and a fine deformation using two sets of pre-defined control points. To evaluate the method, a biplanar X-ray acquisition was obtained from head to foot for 12 volunteers in a standing posture. Up to 172 radio-opaque skin markers were attached to the body surface and used as reference positions. Each envelope was reconstructed three times by three operators. Results showed a bias lower than 7 mm and a confidence interval (95%) of reproducibility lower than 6 mm for all body parts, comparable to other existing methods matching a template onto stereographic photographs. The proposed method offers the possibility of reconstructing body shape in addition to the skeleton using a low dose biplanar X-rays system.